Music teachers professional development needs for effective teaching and learning of music in the primary schools of Kuala Lumpur / Nik Rozalind Nik Hassan - Nik Hassan, Nik Rozalind (2005)
This study was structured around two main objectives: 1) to identify the professional development needs of primary school music teachers; and 2) to propose relevant and suitable in-service courses to fulfil these needs. For this purpose, three methods of data collection were used - namely, documentary reviews, interviews, and a questionnaire were used. There were two sets of respondents in this study: primary school music teachers and ministry officers in charge of music programmes in the schools. A quantitative approach was employed in seeking responses from a sample of 197 music teachers in Kuala Lumpur to provide data to ascertain the knowledge and skills of music teachers in Malaysian primary -schools and the current status of professional development programmes provided. Qualitative data were obtained through interviews with Ministry of Education officers in Teacher Education Division, Curriculum Development Centre, and State Education Department of Kuala Lumpur to lend insights to the quantitative data. Descriptive statistics and inferential analysis were used to analyse the data in relation to the research questions. The concentration of this study was on the following seven major areas of knowledge and skills in music - namely, music theory, singing and aural, playing of musical instruments, music education areas, music history and appreciation, educational technology in music education, and specialised activities in music.